Practice-Based Pedagogies for Counter-Memorial Performance: Teaching to Address and Shift “Plantation Energy” - Chapman, Dasha A. (Performance Matters)

(untitled) (Institute for Performance Studies, Simon Fraser University, 2023)
This article discusses History, Memory, Performance, Place: Activating Davidson’s Submerged Histories, a practice-based course I developed and taught in spring 2020 and spring 2021 at Davidson College, a small liberal arts college twenty miles north of Charlotte, NC, established in 1837 by white slave owners. Drawing together dance, performance studies, and Black studies methodologies, the class centred the body through both practice-based research and critical engagements with power, history, and legacies of white supremacy on campus. Coalescing these three fields amplifies multifaceted practice-based research approaches to antiracist reflective and body-based engagements with history, place, and self. In the class, I brought together embodied creative modalities with archival, historiographic, place-based, theoretical, and dialogic approaches to knowledge production. I facilitated student development of practice-based research projects invested in building new and ongoing relationships to Davidson College’s violent history and its pervasive continuities felt by members of the community in the present. This article considers how practice-based research can be integrated into critical performance pedagogies to contribute to campus historical reckoning projects. Outlining the course methods and integrating student reflections and projects, the article discusses how a process-oriented conception of performance, combined with a “counter-memorial” approach to pedagogy and practice, can underscore ongoing embodied work required to address what one student defined as “plantation energy” on campus.